Lewiston Public Library Services for New Mainer Population - Houston, Joseph (Maine Policy Review, 2024)
The Lewiston Public Library serves a population of nearly 40,000 people, many of whom are recent immigrants. This commentary highlights the services and resources the library has designed to meet the needs of a multilingual community.